Tafsir of Surah Al-Hujurat Verses 9-10 on Bughat (Rebellion) - Dalimunthe, Aidil Putra (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
This journal examines the interpretation of surah Al-Hujurat, verses 9-10, which discuss bughat or rebellion within the context of islamic law. These verses highlight the importance of peace and justice in resolving disputes among muslims. They provide guidelines on how to addrss conflicts between opposing groups, emphasizing the need for reconciliation and decisive action againts the oppressors. Trhe study aims to elaborate on the wording, general, interpretation and specific terms, as well as the reansons for the revelation of the verses and to apply legal reasoning in the context of implementing Islamic law regarding rebellion. The findings indicate that these verses instruct Muslims to reconcile conflicting parties fairly and take firm action againts rebellious groups to guide them back to the right path. The concept of Ishlah or reconciliation, plays a crucial role in conflict resolution both individually and collectively. This journal is expected to provide a deeper understanding of the application of Islamic law in cases of rebellion and disputes among muslims.